What is philosophical progress? - Dellsén, Finnur; Firing, Tina; Lawler, Insa; Norton, James (Philosophy & Phenomenological Research, 2024)
What is it for philosophy to make progress? While various putative forms of philosophical progress have been explored in some depth, this overarching question is rarely addressed explicitly, perhaps because it has been assumed to be intractable or unlikely to have a single, unified answer. In this paper, we aim to show that the question is tractable, that it does admit of a single, unified answer, and that one such answer is plausible. This answer is, roughly, that philosophical progress consists in putting people in a position to increase their understanding, where 'increased understanding' is a matter of better representing the network of dependence relations between phenomena. After identifying four desiderata for an account of philosophical progress, we argue that our account meets the desiderata in a particularly satisfying way. Among other things, the account explains how various other achievements, such as philosophical arguments, counterexamples, and distinctions, may contribute to progress. Finally, we consider the implications of our account for the pressing and contentious question of how much progress has been made in philosophy.